Follow me [large type] - Barber, Kathleen (Thorndike press large print core, 2020)
"Audrey Miller has an enviable new job at the Smithsonian, a body by reformer Pilates, an apartment door with a broken lock, and hundreds of thousands of Instagram followers to bear witness to it all. Having just moved to Washington, DC, Audrey busies herself impressing her new boss, interacting with her online fan base, and staving off a creepy upstairs neighbor with the help of the only two people she knows in town: an ex-boyfriend she can't stay away from and a sorority sister with a high-powered job and a mysterious past. But Audrey's faulty door may be the least of her security concerns. Unbeknownst to her, her move has brought her within striking distance of someone who's obsessively followed her social media presence for years--from her first WordPress blog to her most recent Instagram Story. No longer content to simply follow her carefully curated life from a distance, he consults the dark web for advice on how to make Audrey his and his alone. In his quest to win her heart, nothing is off-limits--and nothing is private. With "compelling, suspenseful" (Liz Nugent) prose, Kathleen Barber's electrifying new thriller will have you scrambling to cover your webcam and digital footprints"--